The Dose Evaluation Of In Vitro and In vivo Test In Kartini Research Reactor Facility Using PHITS Code - Helga Dea Puspita (Indonesian Journal of Physics and Nuclear Applications, 2020)
Dose Evaluation of In Vitro and In Vivo Test In Kartini Reasearch Reactor BNCT Facility Using PHITS Code. this research is about dose analysis for in vitro and in vivo test by using PHITS program. The source of the neutron comes from a reactor that has been modified by previous researchers. In this research used mouse model. Modeling is done by modeling a mouse into a simple cylindrical geometry with a tumor modeled with the sphere geometry inside the cylinder